Regional Economic Outlook, October 2017, Sub-Saharan Africa. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
Growth in sub-Saharan Africa has recovered relative to 2016, but the momentum is weak and per capita incomes are expected to barely increase. Further, vulnerabilities have risen in many countries, adding to the urgency of implementing the fiscal consolidations planned in most countries and with stepped up efforts to strengthen growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet